Analysis of vanishing endometrial cancer by pathological types. Issue 8 (9th June 2022) - Görgülü, Gökşen; Doğan Özdaş, Emel; Özdaş, Erol; Sayhan, Sevil; Kuru, Oğuzhan; Gökçü, Mehmet; Sancı, Muzaffer
Abstract: Purpose: We asked why endometrial cancer sometimes vanishes. Methods: A total of 454 patients diagnosed with endometrioid‐type endometrial cancer (EC) (via endometrial sampling) and treated in our clinic over the past 5 years were enrolled. The patients were divided into two groups: vanishing and residual, depending on whether a tumor was detected in the postoperative hysterectomy specimen. Patient age, numbers of pregnancies and deliveries, menopausal status, systemic disease status, hemogram parameters, International Federation of Gynecology and Obstetrics (FIGO) grade, and invasion status (evident on magnetic resonance imaging [MRI]) were compared between the groups. Results: ECs vanished in 42 (9.25%) patients. The vanishing rates were 19.7% (37/187) in FIGO grade 1 patients, 2.1% (5/238) in grade 2 patients, and 0% (0/29) in grade 3 patients. The average age was lower in the vanishing than the residual group, but the premenopausal status and grade 1 tumor rates were higher (both p  < 0.001). An absence of invasion (as revealed by MRI) was more common in the vanishing group ( p  < 0.001). No recurrence developed in the vanishing group, but recurrences were noted in 3.3% (14/412) of the residual group. There were no significant between‐group differences in any of the numbers of pregnancies or births, systemic disease status, or hemogram parameters (all p  > 0.05). Conclusion: Vanishing EC is more likely in premenopausal women with endometrioid grade 1 EC (as revealed by endometrial biopsy) who lack myometrial invasion on MRI.